Systemic inflammation biomarkers during angioedema attacks in hereditary angioedema - Gil-Serrano, Johana; Labrador-Horrillo, Moisés; Galvan-Blasco, Paula; Sala-Cunill, Anna; Bigas, Patricia; Pereira-González, Javier; Luengo, Olga; Cardona, Victoria; Guilarte, Mar (Frontiers in Immunology, 2024)
Background: Hereditary angioedema (HAE) is a rare disease characterized by localized and self-limited angioedema (AE) attacks. A local increase of bradykinin (BK) mediates AE attacks in HAE, however the role of inflammation in HAE has been poorly explored. We aim to analyze the role of inflammatory mediators in HAE patients during AE attacks. Methods: Patients with a confirmed HAE diagnosis due to C1 inhibitor deficiency (HAE-C1INH) or patients F12 gene mutations (HAE-FXII) attending to our outpatient clinic between November-2019 and May-2022 were included. Demographic and clinical characteristics were analyzed. Blood samples were collected both during symptom-free periods (baseline) and during HAE attacks, and acute phase reactants (APR), such as serum amyloid A (SAA), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), D-Dimer and white blood cells were measured. Results: Seventy-eight patients were enrolled in the study, with a predominant representation of women (76%, n=59), and a mean age of 47.8 years (range 6-88). Among them, 67% (n=52) of patients had HAE-C1INH (46 classified as type 1 and 6 as type 2) while 33% (n=26) had HAE-FXII. During attack-free periods, the majority of patients exhibited normal levels of SAA, ESR, D-dimer, ACE and WCC. However, in a subset of patients (16% for SAA, 18% for ESR, and 14.5% for D-dimer), elevations were noted at baseline. Importantly, during HAE attacks, significant increases were observed in SAA in 88% of patients (p< 0.0001 vs. baseline), in ESR in 65% (p= 0.003 vs. baseline) and D-dimer in 71% (p=0.001 vs. baseline) of the patients. A comparison between baseline and acute attack levels in 17 patients revealed significant differences in SAA AA (p<0. 0001), ESR (p<0.0001) and D-dimer (p= 0.004). No significant differences were observed in CRP (p=0.7), ACE (p=0.67) and WCC (p=0.54). These findings remained consistent regardless of HAE type, disease activity or location of angioedema. Conclusion: The systemic increase in APR observed during HAE attacks suggests that inflammation extends beyond the localized edematous area. This finding underscores the potential involvement of inflammatory pathways in HAE and highlights the need for further investigation into their role in the pathophysiology of HAE.